Democracia y medios, una disyuntiva en América Latina. Desde lo micro como un reflejo de lo macro. Caso San Luis Potosí - Navarro Zamora, Lizy (Estudios sobre el Mensaje Periodístico, 2005)
The binomial democracy-media is one of the most important argument to the countries obtain the transition democracy. However, in Latin America only we can see the democracy in the cities, but not in the provinces. The media have the own responsability. This report is an studie about medias in San Luis Potosí. This case symbolize the state of the medias in the provinces of Latin America. While these medias aren´t democratic, the democracy isn´t going to be in all sectors.